2020
DOI: 10.3390/cancers12061408
|View full text |Cite
|
Sign up to set email alerts
|

Linking Obesity with Colorectal Cancer: Epidemiology and Mechanistic Insights

Abstract: The incidence of obesity and colorectal cancer (CRC) has risen rapidly in recent decades. More than 650 million obese and 2 billion overweight individuals are currently living in the world. CRC is the third most common cancer. Obesity is regarded as one of the key environmental risk factors for the pathogenesis of CRC. In the present review, we mainly focus on the epidemiology of obesity and CRC in the world, the United States, and China. We also summarize the molecular mechanisms linking obesity to CRC in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 161 publications
3
79
0
2
Order By: Relevance
“…It is known that the intake of processed/red meat, alcohol consumption, low intake of fruits and starchy vegetables, and smoking are risk factors for CRC [ 1 , 3 ]. Furthermore, there is a growing body of evidence showing that obesity increases the risk of CRC development and progression [ 114 , 115 , 116 , 117 ]. Epidemiological studies have demonstrated that the association between obesity and CRC incidence is stronger in men than in women [ 118 , 119 ].…”
Section: Sex Differences In the Incidence Of Major Gastrointestinamentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the intake of processed/red meat, alcohol consumption, low intake of fruits and starchy vegetables, and smoking are risk factors for CRC [ 1 , 3 ]. Furthermore, there is a growing body of evidence showing that obesity increases the risk of CRC development and progression [ 114 , 115 , 116 , 117 ]. Epidemiological studies have demonstrated that the association between obesity and CRC incidence is stronger in men than in women [ 118 , 119 ].…”
Section: Sex Differences In the Incidence Of Major Gastrointestinamentioning
confidence: 99%
“…It has been noted that estrogen affects the risk of CRC depending on the stage of CRC development; estrogen enhances ER-β expression to inhibit colon tumorigenesis in the early disease stages, whereas in the late disease stages, it stimulates ER-α expression, resulting in tumor progression [ 132 ]. Thus, it appears that obesity-induced elevation in estrogen levels might have a protective effect on CRC risk through the activation of ER-β [ 114 , 132 ]. In addition, the administration of exogenous estrogens (hormone replacement therapy) shows a protective effect against CRC [ 135 ].…”
Section: Sex Differences In the Incidence Of Major Gastrointestinamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some important clinical factors and lifestyle habits, such as dietary habits, obesity, smoking, and diabetes, were not included in our analysis. However, these factors in uenced the prognoses of patients with colorectal cancer [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…The cause of CRC is not fully understood; it is believed to be multifactorial, and accumulated evidence suggests that certain risk factors are linked to the disease [ 5 ]. For example, genetic factors (family history, inherited syndromes, racial and ethnic background), lifestyle (diet, smoking, and alcohol use), and other illness histories (inflammatory bowel diseases, colon polyps, obesity, type II diabetes) are reported to be strongly correlated with the formation of colon cancer [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%